2006
DOI: 10.1002/cncr.21712
|View full text |Cite
|
Sign up to set email alerts
|

uCyt+/ImmunoCyt™ in the detection of recurrent urothelial carcinoma

Abstract: Objective To systematically identify and appraise the existing literature on the association between polymyalgia rheumatica (PMR) and vascular disease. Methods The Medline, Embase, CINAHL, and Cochrane databases were searched from inception to September 2010. Search criteria included observational studies containing patients with isolated PMR reporting on a vascular outcome. Data were extracted and articles were assessed for quality. Results The database search identified 545 articles. Eight articles reporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(23 citation statements)
references
References 100 publications
1
21
0
1
Order By: Relevance
“…In addition, due to the low risk of tumor progression, marker-guided surveillance could significantly reduce the number of control cystoscopies without placing patients at significant risk. However, to date only one prospective trial using a marker-guided surveillance protocol has been performed [116]. Information from this study, however, is still preliminary and does not yet permit recommendation of this procedure for clinical routine use.…”
Section: Key Questionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, due to the low risk of tumor progression, marker-guided surveillance could significantly reduce the number of control cystoscopies without placing patients at significant risk. However, to date only one prospective trial using a marker-guided surveillance protocol has been performed [116]. Information from this study, however, is still preliminary and does not yet permit recommendation of this procedure for clinical routine use.…”
Section: Key Questionsmentioning
confidence: 99%
“…There was one prospective trial on marker-guided follow-up providing information that may be classified as LoE grade 1b [116,117] according to the Oxford classification for diagnostic procedures [25]. The very same trial was classified as a phase III trial concerning the IBCN classification on marker development [8], while all remaining studies were considered phase II.…”
Section: Cell-based Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…One candidate biomarker is immunocytology, which uses three fluorescently labelled monoclonal antibodies directed against UCB-associated antigens (carcinoembryonic antigen and two bladder tumor–associated mucins). Previous multicentre studies have demonstrated that immunocytology has a higher sensitivity than urinary cytology in the surveillance of UCB patients, especially for low-grade tumors [5,8], leading to US Food and Drug Administration approval for its use in conjunction with cytology for surveillance. Several small single-institution studies have suggested that immunocytology may also perform well in the detection of UCB in patients with painless hematuria [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The overall sensitivity of this combination ranges from 40% to 92% and specificity from 62% to 84%. [3032] Studies by Mian et al , 942 patients,[33] Pfister et al , - a French multicenter study of 694 patients[34] and Messing et al , a multicenter study in USA 341 patients[35] confirm the findings of improved sensitivity and specificity with this combination when used in the follow-up of the patients with bladder cancer. This combination of ImmunoCyt and cytology has been studied to replace the cystocopy in the surveillance of Ta, low-grade lesions by Lodde et al .…”
Section: Discussionmentioning
confidence: 86%